2005
DOI: 10.1097/01.prs.0000189205.85968.12
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignant Transformation of Congenital Melanocytic Nevi: A Retrospective Nationwide Study from the Netherlands

Abstract: Our study shows that congenital melanocytic nevi have a significantly higher risk of developing a malignant melanoma compared with the age-, sex-, calendar-period-specific reference data from The Netherlands Cancer Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 29 publications
(30 reference statements)
0
66
0
1
Order By: Relevance
“…101,102 However, most studies show an incidence rate of melanoma in small and medium CMN of\1%. 3,5,19,[103][104][105][106][107] This compares with a general lifetime risk of MM in the United States of 1.97%. 108 Concerning medium-sized CMN, a prospective study of 230 (1.5-19.9 cm) CMN with an average follow-up of 6.7 years to an average age of 25.5 years found that no MM developed in any of the lesions.…”
Section: Small and Medium Cmnmentioning
confidence: 92%
“…101,102 However, most studies show an incidence rate of melanoma in small and medium CMN of\1%. 3,5,19,[103][104][105][106][107] This compares with a general lifetime risk of MM in the United States of 1.97%. 108 Concerning medium-sized CMN, a prospective study of 230 (1.5-19.9 cm) CMN with an average follow-up of 6.7 years to an average age of 25.5 years found that no MM developed in any of the lesions.…”
Section: Small and Medium Cmnmentioning
confidence: 92%
“…Only congenital melanocytic nevi larger than 20 cm in diameter (called “giant nevi”) have a particularly high malignant risk; divided nevi are generally small to medium-sized and are thus at low risk [11]. To our knowledge, 2 cases of melanoma arising on a preexisting divided nevus have been reported to date.…”
Section: Discussionmentioning
confidence: 98%
“…This has been modified to define large lesions as those that are 11 cm to 20 cm in diameter, and naevi larger than 20 cm are considered as giant lesions [4] . As there is a risk of malignant degeneration associated with large and giant CMN (reported to reach up to 12 percent) [5,6] , it is common practice to completely excise such lesions. It is also thought that surgical excision may reduce the risk of malignant degeneration.…”
Section: Introductionmentioning
confidence: 99%